2014
DOI: 10.1097/sla.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

The Initial Response to the Boston Marathon Bombing

Abstract: Objective We discuss the strengths of the medical response to the Boston Marathon bombings that led to the excellent outcomes. Potential shortcomings were recognized, and lessons learned will provide a foundation for further improvements applicable to all institutions. Background Multiple casualty incidents from natural or man-made incidents remain a constant global threat. Adequate preparation and the appropriate alignment of resources with immediate needs remain the key to optimal outcomes. Methods A col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(39 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…This highlights the importance of effective and on-site intervention of the EMS system, as in the Boston Marathon bombing. [12] Although our hospital covered 10% of all armed injuries, we observed that our patient care quality improved; however, the disaster management principles were violated due to a relatively low number of patients presenting to the ED in a short period. Fifteen patients with a mean ISS score of 4 were followed in the ED setting for eight hours or more.…”
Section: Discussionmentioning
confidence: 90%
“…This highlights the importance of effective and on-site intervention of the EMS system, as in the Boston Marathon bombing. [12] Although our hospital covered 10% of all armed injuries, we observed that our patient care quality improved; however, the disaster management principles were violated due to a relatively low number of patients presenting to the ED in a short period. Fifteen patients with a mean ISS score of 4 were followed in the ED setting for eight hours or more.…”
Section: Discussionmentioning
confidence: 90%
“…The authors found that those with insensate lower limbs who underwent reconstruction had proportionally similar plantar sensation on testing at two years when compared to those who had intact plantar sensation prior to reconstruction [13] . Adding complexity to the situation, delayed access to patients at the location of disasters interrupts transport and evaluation and lengthens ischemia time, thereby increasing risk of compartment syndrome and rates of amputation [6,14] .…”
Section: Discussionmentioning
confidence: 99%
“…The ground-level positioning and shrapnel components of the explosives lead to significant extremity trauma [5] . In total, 66% of admitted patients had lower extremity soft tissue and/or bony injuries [6] .…”
Section: Boston Bombingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, trauma care systems should also be established for potential mass casualty incidents. For example, after the Boston Marathon bombing in 2013, 26 facilities received patients 21 ) . After the 2015 terror attack in Paris, 16 facilities received emergency patients 22 ) .…”
Section: Discussionmentioning
confidence: 99%